Chapter Nanoimprint Lithography - Next Generation Nanopatterning Methods for Nanophotonics Fabrication - Viheril, Jukka (InTechOpen, 2010)
The application of different electrochemical techniques to surfactant systems, namely polarography and cyclic voltammetry, differential capacitance, chronocoulometry and electrochemical impedance spectroscopy, is reviewed.